2018
DOI: 10.1080/13645579.2018.1434866
|View full text |Cite
|
Sign up to set email alerts
|

Learning from failure: are practitioner researchers the answer when conducting research on sensitive topics with vulnerable children and young people?

Abstract: Research that is concerned with sensitive topics such as loss and bereavement can be ethically and methodologically challenging at the best of times (Cook, 1995; Dyregrov, 2004; Stroebe, Stroebe, & Schut, 2003). As Dyregrov observes: "It is well documented that research proposals in this field are much more likely to be rejected by International Review Boards compared to other proposals…" (2004, p. 391). Concerns include: the risk of causing additional distress or retraumatisation for participants

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 63 publications
0
23
0
Order By: Relevance
“…In each school, it was agreed that the participating adult should be the teaching assistant who was providing support to the pupil participant. As a way of addressing possible power imbalances in the research design (Vaswani 2018), adult and child participants were asked to agree upon a method for the collection of video material and identify suitable learning activities to record. In one school, the camera system Swivl, which was already in operation in classrooms, was identified as a suitable method for the recording of learning interactions that took place in the classroom.…”
Section: Methodsmentioning
confidence: 99%
“…In each school, it was agreed that the participating adult should be the teaching assistant who was providing support to the pupil participant. As a way of addressing possible power imbalances in the research design (Vaswani 2018), adult and child participants were asked to agree upon a method for the collection of video material and identify suitable learning activities to record. In one school, the camera system Swivl, which was already in operation in classrooms, was identified as a suitable method for the recording of learning interactions that took place in the classroom.…”
Section: Methodsmentioning
confidence: 99%
“…While there was some discussion of the blurred and overlapping roles of the practitioner researcher, some evidence suggested that participants might experience the research process as therapeutic. Research being conducted by a familiar professional might also help reduce the number of people to whom the participant reveals sensitive information (Vaswani, 2018). This might be a way of taking care of and protecting potentially vulnerable participants.…”
Section: Theme 3: Researcher Rolementioning
confidence: 99%
“…Researching children (Vaswani, 2018) and children's sexuality (Flanagan, 2012) demands a sensitive approach. In an attempt to reduce the power imbalance between herself and the children participating in her research, Vaswani (2018) used photoelicitation and shared with the children how and what was to be discussed.…”
Section: Theme 4: Participant Vulnerabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, 'many accounts of research practice (not least guidelines to "research ethics") reproduce an idealistic vision of research' (Horton, 2008, p. 378). Drawing on Rose (1997), Horton (2008, p. 365) observes that 'the acknowledgement of "failure" and uncertainty can often be revelatory and productive' (see also Ross & Call-Cummings, 2019;Vaswani, 2018).…”
Section: Introductionmentioning
confidence: 99%